Blood miR-21 and miR-26 tailor a good diagnostic model for childhood asthma: Diagnostic model for childhood asthma - Lu, Lidang; Zheng, Guozhong; Lin, Yuanjing (Cellular and Molecular Biology, 2023)
This study was to investigate the relationships between blood miR-21/26a with the prevalence and severity of childhood asthma (CAMP). For this purpose, 123 children with allergic asthma (AZ) from June 2018 to June 2020, and 60 contemporaneous healthy children for reference, were enrolled. Lung function was detected using a portable pediatric spirometer and AZ severity was evaluated. Blood samples of admissions were collected to quantify the expression degrees of miR-21 and miR-26a. Logistic regression analysis and model were constructed. Results showed that (1) CAMP had higher MiR-21 expression and lower MiR-26a expression than healthy controls; (2) The severity of AZ, evidenced by FEV1/PV, significantly correlated with miR-21(Y=-3.825X+102.6, P<0.001) and miR-26a (Y=10.43X+54.29, P<0.001); (3) The prevalence of AZ-related to miR-21 (OR=4.180, P<0.001) and miR-26a (OR=0.058, P<0.001) after adjusting for cofounders. (4) the expression levels of miR-21/26a had a good diagnostic potential for AZ (AUC are 0.85 and 0.94, respectively). In conclusion, Blood miRNA-21 and miR-26a are promising biomarkers for the diagnosis and severity of CAMP.